The adjusted Fisk Weibull distribution: properties and applications. (2nd January 2018) - Okorie, Idika E.; Akpanta, Anthony C.; Ohakwe, Johnson; Chikezie, David C.; Obi, Eunice O.
Abstract: We define a new lifetime distribution from a direct cumulative distribution function composition of the two parameter Fisk distribution and two parameter Weibull distribution with an asymptotic adjustment. The new four parameter distribution is called the adjusted Fisk Weibull (AFW) distribution. The AFW distribution is analytically appealing and some of its statistical properties are expressed in closed forms. The maximum likelihood method of parameter estimation was used to estimate the parameters of the new distribution and the usefulness and possible applications of the distribution was illustrated with two real and uncensored data-sets.